Cyber security breaches survey: combined dataset, 2016-2022 (UK Data Service, 2022)
These surveys have been conducted annually since 2016 to understand the views of UK organisations on cyber security. Data are collected on topics including online use; attitudes of organisations to cyber security and awareness of Government initiatives; approaches to cyber security (including investment and processes); incidences and impact of a cyber security breach or attack; and how breaches are dealt with by the organisation. This information helps to inform Government policy towards organisations, including how best to target key messages to businesses and charities so that they are cyber secure (and so that the UK is the safest place in the world to do business online). The study is funded by the DCMS as part of the government's £2.6 billion National Cyber Strategy 2022 to protect and promote the UK in cyber space. The underlying data are useful for researchers to better understand the response across a range of organisations and for wider comparability over time. The survey originally only covered businesses but was expanded to include charities from the 2018 survey onwards. From 2020, the survey includes a sample of education institutions (primary and secondary schools, further and higher education). Please note that the UK Data Service only holds datasets on each specific year from 2018 onwards. Cyber Security Breaches Survey: Combined Dataset, 2016-2022 includes data from 2016 to 2022. This is cross-sectional data only and not all variables are included in all years. For longitudinal data, please access the Cyber Security Longitudinal Survey: Wave 1, 2021 (available from the UK Data Archive under SN 8969) and onwards.